Exploring Inclusive Education through Narratives: Addressing Challenges for Special Needs Students - Netty Huzniati Andas; Jamil Khan; Rafiullah Amin (Yayasan Adra Karima Hubbi, 2026)
Background. Inclusive education is a critical framework that aims to integrate students with special needs into mainstream classrooms. Despite its significance, students with special needs often encounter barriers that hinder their academic and social development. These challenges are multifaceted, encompassing physical, emotional, and educational obstacles. Purpose. This study explores the role of narratives in inclusive education, specifically addressing the challenges faced by students with special needs. By examining the stories of these students, the research aims to highlight how narrative sharing can contribute to overcoming barriers and fostering an inclusive, supportive learning environment. Method. A qualitative research design was employed, using semi-structured interviews, focus group discussions, and narrative diaries to collect data from 30 students with special needs and 15 teachers. Thematic analysis was applied to identify key themes that emerged from the narratives shared by participants. Results. The findings indicate that narrative sharing enhances emotional engagement, reduces stigma, and promotes a sense of belonging among students with special needs. Teachers and peers demonstrated greater empathy, and students with special needs showed increased academic and social participation Conclusion. The study emphasizes the transformative potential of narrative-based practices in inclusive education, contributing to the empowerment of both students and educators.